Predictors of Television Programmes Quality in Tanzania: Analysis of Stakeholders ' Perspectives - Eliah, Victor (University of Dar es Salaam Library Journal, 2022)
There have been complaints over the quality of television programmes in Tanzania from various groups including; professionals, viewers, television programme sponsors and media authorities. Recognizing the role played by the availability of diverse programme quality perspectives on the amount such compliments, this study sought to establish an understanding on how stakeholders view quality in TV programmes. The study triangulated quantitative and qualitative methods in order to establish a better understanding. The study involved a total of 70 respondents that included; television programmes producers, television programmes viewers, programme sponsors, television programmes managers, and telecom/electronics engineers/technicians. The study has used questionnaire and interviews to collect data from these respondents. Based on the data collected, the study has found that the term "quality" in the context of television production is "erratic" due to the absence of specific standards for measuring it save for different perspectives of professionalism, viewers, business/sponsorships, editorial polices, creativity and cultural orientations. In order to sustain quality control, the study recommends among other things, the establishment of quality control boards or quality assurance unit by the government to spearheading standards in television production and bridge professionalism.